A Review of Rhythm in Persian Translations of the Works of Christian Bobin: Mahvash Ghavimi’s Translation of Geai and Isabelle Bruges - Saber Mohseni (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to study the question of rhythm in the Persian translations of the work of Christian Bobin, presented by Mahvash Ghavimi. In Bobin’s writings, we meet people who seek happiness, but instead of fighting problems and changing conditions, they accept life as it is. After presenting the thought that Bobin confides to his readers in a simple and fluid style, we approach the question of rhythm as it is treated in the writings of Henri Meschonnic, a French translator. According to him, every text has its own rhythm which plays a crucial role in its significance. The translator must discover the factors involved in the significance of the text and recreate them in the translated text. We are then interested in studying the translation of two books of Bobin, entitled Geai and Isabelle Bruges, to see how the translator overcame the problems of recreating the rhythm.